2001
DOI: 10.1034/j.1600-0846.2001.70403.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal imaging in acute herpes zoster or post‐zoster neuralgia

Abstract: Thermal asymmetry of the skin is a common finding in patients with acute herpes. However, the thermal patterns seem to correlate better with the duration of the disease than with the intensity of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…Two days later (day 0 [D0]), a pruritic urticarial plaque was noted on the left side of the chest. [2][3][4] In the present case, serial follow-up was performed for the first time, to our knowledge, and revealed interesting findings. On the next day (D2), skin lesions appeared on the back, and the first thermogram was performed (Figure 1).…”
Section: Thermographic Follow-up Of a Mild Case Of Herpes Zostermentioning
confidence: 72%
See 2 more Smart Citations
“…Two days later (day 0 [D0]), a pruritic urticarial plaque was noted on the left side of the chest. [2][3][4] In the present case, serial follow-up was performed for the first time, to our knowledge, and revealed interesting findings. On the next day (D2), skin lesions appeared on the back, and the first thermogram was performed (Figure 1).…”
Section: Thermographic Follow-up Of a Mild Case Of Herpes Zostermentioning
confidence: 72%
“…A 39-year-old Korean man reported dysesthesia of the left axilla. [2][3][4] However, no significant results were identified except for the chronologic correlation with the duration of the disease. One day later (D1), tiny vesicles began to develop, and pain became evident.…”
Section: Thermographic Follow-up Of a Mild Case Of Herpes Zostermentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared thermography shows physiological rather than anatomic changes (7). Thermal asymmetry of the skin, in which the affected area is either warmer or cooler than the contralateral site, has been described in patients suffering from acute HZ (7–9). One study showed that reduced temperature on the affected side, as determined by infrared thermal imaging, is a predictor of PHN.…”
mentioning
confidence: 99%
“…Hitherto, HRIT has been rarely used in inflammatory skin diseases of infectious origin. Ammer et al applied whole body HRIT to measure asymmetry of skin temperature in patients with acute herpes zoster and postherpetic neuralgia [20]. Arenas et al used long-distance infrared thermal imaging for the diagnosis of disseminated mange (animal scabies) in wild Pyrenean goats [12].…”
Section: Discussionmentioning
confidence: 99%